THE POTENTIAL FOR INTER-INSTITUTIONAL COOPERATION FOR SHARIA ACTUARY NON-CERTIFICATION PROGRAMS FOR SHARIA INSURANCE IN INDONESIA - Alfiah Hasanah; FNU Cupian; Eko Fajar Cahyono; Lina Nugraha Rani (Airlangga International Journal of Islamic Economics and Finance, 2018)
This study aims to explore the potential model of collaboration among institutions such as the Financial Services Authority  (OJK) as regulators, higher education institutions, general higher education institutions and religious higher education, sharia insurance industry associations, actuary professional associations and sharia insurance companies to carry out non-sharia certification of the sharia actuary profession. This study uses descriptive qualitative approach and literature study method. The results of the study recommend that certification programs that span sharia actuaries require several institutional roles includingFinancial Services Authority (OJK), National Sharia Council (DSN), Indonesian Ulema Council (MUI), Indonesian Syariah Insurance Association (AASI) and Indonesian Actuary Association (PAI). Each agency has their respective duties and functions such as regulators, prospective actuary providers, distance education providers, certification providers, and material providers.